Prosedur dan Tanggung Jawab PT Jatim Grha Utama dalam Kegiatan Operasi Pasar: Menjaga Ketersediaan dan Stabilitas Harga Bahan Pangan Melalui Kegiatan UMKM - Audry Valencia Jeta Zafira; Bagus Nuari Harmawan (Pusat Riset dan Inovasi Nasional, 2023)
In this research, in stabilizing the economy in an area in Surabaya and targeting market operating procedures, the Government and PT. Jatim Grha Utama also has a role in advancing the economy of the people of Surabaya. The government continues to push for price stabilization measures to reduce the prices of a number of foodstuffs which show an upward trend until the end of the year. As a concrete step to ease the burden on the community in meeting their basic food needs, the Coordinating Ministry for the Economy has taken several comprehensive and holistic steps to analyze and overcome the various problems mentioned above through policy and tactical steps. Domain in the form of market power. Apart from food prices, rising fertilizer prices are also a concern. The Coordinating Minister for Airlangga also conducted a review of a fertilizer kiosk to show the government's commitment to ensuring the availability of fertilizer for farmers and increasing agricultural productivity and competitiveness. In addition, the government's role in determining market prices directly is to set minimum price limits and maximum price limits. While the government's role in determining market prices indirectly is by imposing taxes on luxury goods and providing subsidies to producers. In this case, market traders also participate successively and contribute with the government in stabilizing food prices in the market, thereby creating and implementing an independent economy for the people of Surabaya and stabilizing food prices in Surabaya.